2013
DOI: 10.1002/ccd.25136
|View full text |Cite
|
Sign up to set email alerts
|

Two‐week interval optical coherence tomography: Imaging evidence on neointimal coverage completion after implantation of the endeavor zotarolimus‐eluting stent

Abstract: The full circumferential coverage of the vessel wall by the high-signal neointima was found at as early as week 10 after E-ZES implantation, imparting a surrogate index for vascular healing by NIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The ethics loaded with zotarolimus at the dose concentration of 10-mg/mm stent length. The drug is eluted within 15 days of implantation, and concentration within surrounding vascular tissue is not detected already at 30 days after stent deployment (8,9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethics loaded with zotarolimus at the dose concentration of 10-mg/mm stent length. The drug is eluted within 15 days of implantation, and concentration within surrounding vascular tissue is not detected already at 30 days after stent deployment (8,9).…”
Section: Methodsmentioning
confidence: 99%
“…The zotarolimus-eluting Endeavor Sprint stent (E-ZES) is a hydrophilic polymer-based secondgeneration device with a unique drug fast-release profile (8), resulting in less powerful inhibition of intimal hyperplasia, but also in a rapid and/or complete stent strut coverage. This characteristic raises the possibility that it might be feasible to shorten DAPT duration while maintaining superior efficacy compared with BMS (9). The ZEUS (Zotarolimus-Eluting Endeavor Sprint Stent in Uncertain DES Candidates) study, which mandated a tailored DAPT duration based on patients' characteristics, showed a lower incidence of major adverse cardiovascular events (MACE) after E-ZES as compared with BMS in uncertain DES recipients.…”
mentioning
confidence: 99%
“…Proper neointimal formation and a lower number of uncovered struts are indicators optimal healing. Previous studies have shown that excessive inhibition of neointimal formation may lead to incomplete endothelialization and an increased proportion of uncovered struts, which could result in late stent thrombosis 28 . Finn et al reported that numerous uncovered struts could activate platelets, posing a significant risk for developing stent thrombosis at later stages 27 .…”
Section: Discussionmentioning
confidence: 99%
“…of uncovered struts, which could result in late stent thrombosis 28. Finn et al reported that numerous uncovered struts could activate platelets, posing a significant risk for developing stent thrombosis at later stages 27.…”
mentioning
confidence: 99%
“…This optimum healing has been measured in terms of apt neointimal formation and lower number of uncovered struts. Previous studies show that excessive inhibition of neointimal formation could cause incomplete endothelialization, which is associated with increased proportion of uncovered struts and the subsequent occurrence of late stent thrombosis 27 . Finn et al reported that a large proportion of uncovered struts have potential to activate platelets, resulting to be major risk factor for developing stent thrombosis at later stages 26 .…”
Section: Discussionmentioning
confidence: 99%